Предмет: Алгебра,
автор: LerchikNais
(x+3)(x-11)+(x+6)во второй степени
Ответы
Автор ответа:
0
(х²+3х-11х-33)+(х²+12х+36)=х²-8х-33+х²+12х+36=2х²+4х+3
Автор ответа:
0
(х + 3)(х - 11) +(х + 6 )^2 =
= x^2 + 3x - 11x - 33 + x^2 + 12x + 36 =
= 2x^2 +4x +3
= x^2 + 3x - 11x - 33 + x^2 + 12x + 36 =
= 2x^2 +4x +3
Похожие вопросы
Предмет: География,
автор: neymna79
Предмет: Литература,
автор: zahust9
Предмет: История,
автор: Railyna
Предмет: Математика,
автор: Hl2003
Предмет: Математика,
автор: shirokihpolina